Regression Analysis of Breaststroke Swim Performance From Physical, Physiological and Energy Parameters - Maulidin, Maulidin; Asmawi, Asmawi; Tangkudung, James (International Journal for Educational and Vocational Studies, 2019)
The purpose of this research was to determine the effect of leg muscle power, maximal oxygen, and achievement motivation on breaststroke swimming athlete. This research used a survey method to see the direct relationship between height variables, leg muscle power, maximal oxygen volume, achievement motivation on breaststroke swimming athletes. The sample used 42 people who were determined by purposive male swimmers aged 15-17 years and had participated in the championship. Performed an all-out 50-m breaststroke swimming test in a 50-m pool. The data analysis technique uses path analysis. The results of the analysis of each variable have direct effects where: Body height has a positive direct effect on swimming skills (R² = 0.308), leg muscle power has a positive direct effect on swimming skills (R² = 0.548), 3) the energy cost of oxygen has an effect positive direct to swimming skills of (R² = 0.519), motivation has a positive direct effect on athlete swimming skills with (R² = 0.419). Of the five-leg muscle power variables that have the greatest influence on breaststroke, swimming speed is 54.8% the remaining 45.2% is caused by other factors such as weather conditions, mental state, nutrition, recovery and health conditions of athletes.